A Program to Provide Decent housing As Social support For Improving the Education Of Children in Underprivileged Families - Manupassa, Royanto; Sahetapy, Petronela; Rolobessy, Mike J; Lopulalan, Dortje L. J. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Housing that is far from decent is still widely used as a place of residence. People in SBB district who are less fortunate do not have land to build a house, especially since land currently has high economic value. The purpose of writing as an indicator in analyzing the extent of the Livable Housing Assistance Program at the Housing and Settlement Area Service of West Seram RegencyPolicy implementation theory is used to answer problems with a qualitative research approach as a form of approach method to conduct in-depth studies on natural object conditions. The results show 1. The resource aspect in the PERKIM field of SBB Regency is quite available in terms of skills and abilities, besides that they are given the opportunity to develop knowledge capacity in improving personality abilities through further education at a higher level. 2. The attitude of the implementer is greatly influenced by the level of knowledge and understanding of the policy and the level of problematic issues that must be resolved as a priority. 3. Communication channels are a form of information used in the interaction of policy implementers and subordinates, namely vertical communication built between leaders and subordinates and coordinative communication with the community receiving the policy. However, what is of serious concern is that communication must be carried out intensively and with full concern and empathy. 4. There is a division of tasks based on SOP, starting from proposals for the construction/repair of RTLH from the Village/Sub-district, RTLH Management, RTLH Verification, Preparation of Recipient Decrees for Assistance, Preparation of RTLH Assistance Administration Documents, Supervision and Distribution Process of Assistance, Implementation of Supervision of RTLH Activities and Construction or Repair, as well as evaluation and reporting.